2000
DOI: 10.1016/s0029-7844(99)00581-5
|View full text |Cite
|
Sign up to set email alerts
|

Gynecologists' training, knowledge, and experiences in genetics: a survey

Abstract: Gynecologists were more knowledgeable about genetic issues pertaining to breast and ovarian cancer than to other cancers or certain adult-onset disorders. Training appeared to increase knowledge. Increased training and affiliation with genetic specialists and others could improve gynecologists' ability to use genetic screening in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 9 publications
4
27
1
Order By: Relevance
“…In addition, attending a required course in genetics did not influence the knowledge score, as it did in the United States. 5,13 More interest in genetics, approximated by taking an elective course in genetics, was related to a higher knowledge score among the GPs and PEDs, which was in contrast with the results of the study in the United States. 5 Full-time faculty members did not score, in contrast with the findings in the United States, a higher knowledge score.…”
Section: Factors Associated With Knowledgecontrasting
confidence: 83%
“…In addition, attending a required course in genetics did not influence the knowledge score, as it did in the United States. 5,13 More interest in genetics, approximated by taking an elective course in genetics, was related to a higher knowledge score among the GPs and PEDs, which was in contrast with the results of the study in the United States. 5 Full-time faculty members did not score, in contrast with the findings in the United States, a higher knowledge score.…”
Section: Factors Associated With Knowledgecontrasting
confidence: 83%
“…In fact, in our sample (as in other studies of health care professionals), exposure to genetics/genomics or PHG training 28,34 (and higher levels of education 35 ) were associated with better genomic knowledge and awareness. Moreover, respondents with CHES certification were more aware of efforts made in health promotion regarding PHG, most likely because of the need to maintain themselves up-to-date for certification purposes.…”
Section: Discussionsupporting
confidence: 60%
“…This association between knowledge scores and gender was not found in other studies on genetics knowledge among physicians in the Netherlands (Baars MJH et al, unpublished data, 2005). 4,6 In general, no differences were found between students from different medical schools, except that students from one medical school (A) scored significantly lower, compared to those from two of the other six medical schools (E and G).…”
Section: Genetic Knowledge Among Medical Studentsmentioning
confidence: 88%
“…Several studies have shown that many nongenetic health care providers lack the necessary knowledge and skills to react appropriately to the increasing demands of patients. [1][2][3][4][5][6][7] One possible cause of this reported lack of knowledge and skills is deficiency in the medical curriculum. In the Netherlands, medical undergraduate education takes a minimum of 6 years of theoretical and practical work at one of eight universities.…”
mentioning
confidence: 99%